Conference on Lasers and Electro-Optics 2022
DOI: 10.1364/cleo_qels.2022.ff1a.6
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-range Optical Trapping and Manipulation in Suspensions via Asymmetric Potentials

Abstract: The well-known counter-propagating optical traps require the beams to be symmetrical for 3D trapping, resulting in a highly-sensitive system. Here, we study an easy-to-align counter-propagating trap with a broken symmetry, demonstrating stable trapping over millimeter-range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a previous study, we addressed the rst question by utilizing dual AsymmetricalCounter-Propagating (ACP) beams along with the use of low-NA components to form the optical trap [42,43]. We showed that the asymmetry introduced in the two CP beam system not only increases trapping stiffness (with respect to traditional CP beam traps) but also allows for the axial scattering forces to be balanced over a wide spatial length.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we addressed the rst question by utilizing dual AsymmetricalCounter-Propagating (ACP) beams along with the use of low-NA components to form the optical trap [42,43]. We showed that the asymmetry introduced in the two CP beam system not only increases trapping stiffness (with respect to traditional CP beam traps) but also allows for the axial scattering forces to be balanced over a wide spatial length.…”
Section: Introductionmentioning
confidence: 99%